A birefringent etalon enhances the Faraday rotation of thin magneto-optical films - E. Almpanis; P.A. Pantazopoulos; N. Papanikolaou; V. Yannopapas; N. Stefanou (Journal of Optics, 2017)
The magneto-optical response of a Faraday-active Fabry–Pérot etalon with birefringent mirrors is studied by means of electrodynamic simulations using the finite-element and the scattering-matrix methods. The specific structure under consideration consists of a magnetic garnet film sandwiched between two metallic layers, patterned with periodically spaced parallel grooves on their outer sides. Our results are analyzed by reference to the properties of the individual structural components and a consistent interpretation of the different spectral features observed is provided. It is shown that, by properly adjusting the geometrical parameters involved, strong Faraday rotation enhancement can be obtained through constructive synergy between the Fabry–Pérot resonant mode of the magneto-optical nanocavity and the slot plasmon mode localized in the grooves.